Experiment Study for Wrist-Wearable Electro-Tactile Display - Xiong Lu; Minxu Lin; Shouchun Wang; Xusheng Hu; Hongbin Yin; Yuxing Yan (Sensors, 2021)
Tactile sensation is a promising information display channel for human beings that involves supplementing or replacing degraded visual or auditory channels. In this paper, a wrist-wearable tactile rendering system based on electro-tactile stimulation is designed for information expression, where a square array with 8 × 8 spherical electrodes is used as the touch panel. To verify and improve this touch-based information display method, the optimal mode for stimulus signals was firstly investigated through comparison experiments, which show that sequential stimuli with consecutive-electrode-in-active mode have a better performance than those with single-electrode-in-active mode. Then, simple Chinese and English characters and 26 English characters’ recognition experiments were carried out and the proposed method was verified with an average recognition rate of 95% and 82%, respectively. This wrist-wearable tactile display system would be a new and promising medium for communication and could be of great value for visually impaired people.